Implementation of Weighted Aggregated Sum Product Assessment (WASPAS) in Determining the Best Graduates - Sonya Malinda Harahap; Iman Judi Tua Situmeang; Siti Hummairoh; Mesran Mesran (STMIK Budi Darma, 2021)
The best graduates are pride or people who are considered capable of selling their soft skills or hard skills after completing their Diploma III (D-III) or Starata 1 (S-1) education. The best graduate degrees selected are obtained from several criteria, such as the Grade Point Average (GPA), Organization, Achievement, Intermediate Semester / Corrective Examination, and Attitude during their education at a university. In determining the best graduate students, sometimes obstacles arise, causing difficulty in determining the best graduates. Therefore, to determine the best graduate, each alternative must have criteria. Which one, Each criterion has a weight that has been determined individually and is carried out by the completion process using the Weighted Aggregated Sum Product Assessment (WASPAS) method for the ranking process. The highest score or ranking will be used as an alternative recommendation that will get the title of the best graduate .